Hydrobiogeochemical Controls on Riparian Nutrient and Greenhouse Gas Dynamics: 10 Years Post‐Restoration1. (June 2014) - Vidon, Philippe; Jacinthe, Pierre‐Andre; Liu, Xiaoqiang; Fisher, Katelin; Baker, Matthew
Abstract Little is known about the impact of agricultural legacy on subsurface biogeochemical processes in the years following restoration of riparian wetlands (WLs). More knowledge is also needed on the relative importance of seasons, precipitation events, and inputs of water and nutrients driving nitrogen (N), phosphorus (P), sulfur (S), and greenhouse gas (GHG) (N2O, CO2, CH4) dynamics in these systems. This investigation of a riparian zone comprising a restored WL area and a nonrestored well‐drained alluvium (AL) area in the United States Midwest revealed that despite successful hydrological restoration a decade earlier, biogeochemical conditions in the WL area remained less anoxic than in natural WLs, and not significantly different from those in the AL area. No significant differences in N, P, S, and C compound concentrations or fluxes were observed between the AL and WL areas. Over the duration of the study, nitrate (NO3−) and soluble reactive phosphorus appeared to be primarily driven by hillslope contributions. Ammonium (NH4+), sulfate (SO42−), and CO2 responded strongly to seasonal changes in biogeochemical conditions in the riparian zone, while N2O and CH4 fluxes were most influenced by large rewetting events. Overall, our results challenge overly simplistic assumptions derived from direct interpretation of redox thermodynamics, and show complex patterns of solutes and GHGs at the riparian zone scale.